2017
DOI: 10.1371/journal.pone.0178788
|View full text |Cite
|
Sign up to set email alerts
|

Effects of obesogenic diet and estradiol on dorsal raphe gene expression in old female macaques

Abstract: The beneficial effects of bioidentical ovarian steroid hormone therapy (HT) during the perimenopause are gaining recognition. However, the positive effects of estrogen (E) plus or minus progesterone (P) administration to ovariectomized (Ovx) lab animals were recognized in multiple systems for years before clinical trials could adequately duplicate the results. Moreover, very large numbers of women are often needed to find statistically significant results in clinical trials of HT; and there are still opposing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 90 publications
(101 reference statements)
0
5
1
Order By: Relevance
“…Together, these findings suggest that neuroprotective effects of E2 are retained in early-MA even in the presence of a preexisting obese state. In apparent contrast to our observations, recent work in aged female macaques showed that positive effects of E2 on object recognition memory were blunted by obesogenic diet (Bethea et al, 2017). This lack of concordance suggests the possibility of a complex relationship between obesity and E2 neural efficacy during aging that may be affected by several parameters, including specific aspects of diet, aging, and neural measure.…”
Section: Discussioncontrasting
confidence: 99%
“…Together, these findings suggest that neuroprotective effects of E2 are retained in early-MA even in the presence of a preexisting obese state. In apparent contrast to our observations, recent work in aged female macaques showed that positive effects of E2 on object recognition memory were blunted by obesogenic diet (Bethea et al, 2017). This lack of concordance suggests the possibility of a complex relationship between obesity and E2 neural efficacy during aging that may be affected by several parameters, including specific aspects of diet, aging, and neural measure.…”
Section: Discussioncontrasting
confidence: 99%
“…When serum E levels declined below 50 pg/ml, the implants were replaced. There is a surge of E immediately after implantation that gradually declines and stabilizes; so, monitoring every 2 months enabled us to maintain the goal on average [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…The behavioral observations were obtained as part of a larger study involving these animals ([ 16 ]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of examples in medicine that synthetically produced chemicals (drugs) may influence the development of adiposity. This usually adverse effect of pharmaceuticals is evidenced in glucocorticoids, estrogens, some antidiabetics (such as insulin, sulphonylureas, thiazolidinediones, glitazones), thyreostatics, dopaminergic blockers, beta sympathetic blockers, and, in some drugs, from the groups of tricyclic antidepressants, selective serotonin re-uptake inhibitors, atypical antipsychotic medicines, antiepileptics, Biomolecules 2022, 12, 680 2 of 18 neuropeptides, and eutonics of the gastrointestinal tract [2][3][4][5][6][7][8]. However, not only medicines, but many compounds introduced in mega doses to the environment over the last decades by human production, were recognized to be able to act as obesogens.…”
Section: Introductionmentioning
confidence: 99%